Ameliorating Performance of UAE Projects by Technological Collaboration of Construction Entities - Wajeeha Hasnain; Urooj Pasha (iRASD Journal of Management)
The construction industry is comprised of various entities that are a collection of different teams with varying expertise. These entities are supposed to work together on a particular project to achieve a common goal. This research investigates the association of Information Technology and the Degree of Functional Integration with the performance of Construction Projects. The United Arab Emirates is known for its Construction wonders and mega structures supported by massive investments. Therefore, the construction industry of the United Arab Emirates is selected to study the role Information Technology application in the Performance of the Construction firms when studied together with prevailing function integration norms within the organizations. The collected data is then analyzed through SPSS. It is revealed based on the regression results that Information Technology Capability and Degree of Functional Integration of including entities i.e., Owner, Contractor, and Supplier have positive effects on the performance of Construction projects. In the end findings are supported by a conceptual model that explicitly explains the Procedural levels of Concept implementation.